A Note on Adaptability of Species to Sandy Soil of Purnea and Bettiah (Bihar) - Sinha, K. N.; Mishra, P. R. (Indian Forester, 1966)
Studies on soil and its moisture conditions revealed some of the probable causes of failure of bamboo in sandy soil of Purnea and Bettiah Districts of Bihar. The investigation revealed that the success of any species on a particular soil depends largely on the degree of positive correlation of its initial root system with the moisture content of the soil. Deep rooted species fulfil this promise in areas where soil of the upper layers is porous, coarse and non-retentive of moisture and as such are the most adaptable ones to the area under examination.